2017
DOI: 10.1002/2017wr020749
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and uncertainty analysis of a parsimonious floodplain surface water‐groundwater interaction model

Abstract: Floodplains provide a variety of hydrological and ecological functions and are therefore of great importance. The flooding frequency, as well as the height and duration of inundations are particularly relevant for ecosystem states and are dependent on the exchange between surface water and groundwater. In this study, we developed a fully distributed model approach to simulate distributed groundwater levels in a floodplain in Hesse, Germany (14.8 km2). To overcome the problem of large computation times, we simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…The same results have also been observed in other applications of the HBV model for the Rhine River (e.g., [43]). We found that the water level of the Rhine River is the primary driving variable for the groundwater-surface water model, as the Rhine River is known to be directly connected with the groundwater of the floodplain and is mainly responsible for the groundwater level changes [34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The same results have also been observed in other applications of the HBV model for the Rhine River (e.g., [43]). We found that the water level of the Rhine River is the primary driving variable for the groundwater-surface water model, as the Rhine River is known to be directly connected with the groundwater of the floodplain and is mainly responsible for the groundwater level changes [34].…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we modified a previously-developed parsimonious, physically-based surface water-groundwater model to simulate flood characteristics in the floodplain [34]. The model is built with the catchment modeling framework (CMF), version v0.1315 [35,36] and includes the interaction between surface water and groundwater flow.…”
Section: Surface Water-groundwater Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…It 15 can be used for subsurface and surface water fluxes, surface-atmosphere exchange and solute transport. So far, it has been applied in studies to better understand hydrological processes (Holländer et al, 2009;Maier et al, 2017;Orlowski et al, 2016;Windhorst et al, 2014), to simulate solute transport (Djabelkhir et al, 2017;Kraft et al, 2010) and to capture hydrological lateral and vertical transport processes in coupled complex ecosystem models (Haas et al, 2013;Houska et al, 2014Houska et al, , 2017Kellner et al, 2017). 20…”
Section: Introduction 20mentioning
confidence: 99%